Strongyloidiasis duodenum: A histopathological study - Rimi Pandey; Padam Kumari Agarwal; Prashant Katiyar (Wolters Kluwer Medknow Publications, 2021)
Strongyloides stercoralis is an intestinal nematode that infects humans, percutaneously and has a complex life cycle. We report a case of a thirty year old male presenting with chief complaints of profuse watery diarrhoea, abdominal fullness, loss of appetite, creepy abdominal pain and low-grade fever for the last one month. He was on corticosteroids for systemic sclerosis. Endoscopy showed thickened and oedematous duodenal folds with pinpoint areas of bleeding and multiple ulcerations on the duodenal mucosa. Histopathologial examination of duodenal biopsy revealed infestation by Strongyloides stercoralis in the duodenum, the duodenal mucosal glands were occupied by various parts of parasite. The patient was successfully treated and had uneventful recovery.